A Study on the utilization of areca nut husk fiber as a natural fibre reinforcement in composite applications: A systematic literature review - Zulhan Insan Makruf; Wanda Afnison; Bulkia Rahim (Researcher and Lecturer Society, 2024)
This paper presents a systematic literature review of published research on the use of areca nut bark fibres as a reinforcing material in polymer composites. A total of 22 research articles published in Scopus-indexed journals were identified and analysed in depth. In addition, this article presents current issues related to areca nut husk fibre (ANHF) as a reinforcement in composites using the VOSviewer tool. In this article, the authors explains the processing stages of ANHF before it is used as a reinforcement in composites. The chemical treatments carried out are also summarised in this article. Not all types of resins available on the market have been used as matrix in the manufacture of areca nut shell fibre composites. The use of additives derived from natural materials has also been found to be effective in improving the quality of ANHF composites. This article also highlights the need for further research to improve the quality of areca nut husk fibre composites and discusses the unanswered aspects of the published research.